Laser speckle contrast imaging for perfusion monitoring during surgical reconstruction of anorectal malformations - Pernilla Stenström; Rafi Sheikh; Kristine Hagelsteen; Johanna Wennström Berggren; Malin Malmsjö (Elsevier, 2021)
Anorectal malformations (ARM) are a spectrum of congenital malformations, specifically defined by the absence of a normal anal opening. These conditions are treated surgically by posterior sagittal anorectoplasty and, in cases with perineal fistulas, perineal skin advancement is required to cover the tissue defect. Complications involving wound dehiscence are frequent, and may be due to stretching of the skin, although the exact cause has not been determined. We have used laser speckle contrast imaging to monitor the surgical repair of a recto-prostatic ARM in a 5-week-old boy, and found that perfusion is reduced upon stretching the perineal skin. The lack of oxygen and nutrients to the wound edge may impair healing and increase the risk of infection. The use of perfusion monitoring during surgical reconstruction of ARM may facilitate surgical decision-making and reduce complications in the future.